Investigation of Resistivity, Magnetic Susceptibility and Dielectric Properties of Nanocrystalline Ni-Mn-Zn Ferrites - Gawas U.B.; Kothawale M.M.; Pednekar R.; Meena S.S.; Prasad N.K.; Alla S.K. (My University, 2025)
Ni0.6−xMnxZn0.4Fe2O4 (x = 0.0–0.6) samples were synthesized using a combustion technique involving a mixture of hexamine and metal nitrate. XRD measurements confirmed the single-phase formation. The lattice parameters were found to increase gradually with increasing Mn substitution. The peak broadening observed for these ferrites indicates their nanocrystalline nature. FTIR spectra display two absorption bands which are characteristics of M–O stretching in tetrahedral and octahedral sites in the spinel lattice. SEM observations show that the particles occur as loose agglomerates. Lower DC resistivity values in the range of 106 to 107 Ωcm observed at room temperature suggests the protonic conductivity due to moisture trapped inside the pores. The resistivity was found to decrease with increasing Mn substitution at higher temperatures. AC susceptibility studies reveal the presence of clusters of both superparamagnetic and single-domain particles. Curie temperatures were found to decrease with increasing Mn concentration. The low dielectric losses of about 10−2 in the higher frequency region were observed. © 2016, Springer Science+Business Media New York.